Juridical Review of Construction Permit Boundaries in Marine Areas: A Case Study on the Coastal Community of Nii Tanasa Village, Lalonggasumeeto District, Konawe Regency - Jumiati Ukkas; nur Intan Nur Intan; Heryanti Heryanti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Coastal communities occupy a complex legal and ecological setting where settlement, livelihood activities, and infrastructure development intersect with sensitive marine ecosystems. In Indonesia, marine construction activities are regulated through permitting systems intended to ensure environmental protection and sustainable coastal development. However, compliance remains limited in many coastal areas. Objectives: This study assessed community understanding of marine construction permit regulations in Nii Tanasa Village, Konawe Regency, including awareness, procedural knowledge, influencing factors, and the perceived impacts of non-compliant construction activities. Methods: A socio-legal research approach was employed, combining doctrinal legal analysis with empirical methods. Data were collected from coastal residents and analyzed using descriptive and multivariate statistical techniques. Results: Most respondents demonstrated low legal understanding of marine construction permits. Approximately 77.7% had low awareness of relevant regulations, while 88.9% were unable to identify the proper permitting procedures. Education level, economic condition, participation in government socialization programs, and compliance with customary law significantly influenced legal understanding (p < .05). Respondents also reported ecological and social impacts of unregulated construction, including mangrove degradation (42.2%), coral reef damage (35.6%), and community conflicts (31.1%). Following a government socialization program, legal understanding increased by 50–68 percentage points. Conclusion: Legal understanding of marine construction permits remains inadequate among coastal residents. Continuous outreach, culturally sensitive legal education, and integration of customary law are needed to strengthen compliance and support sustainable coastal management. Keywords: coastal communities; customary law; legal awareness; marine construction permits; socio-legal research.